The prevalence of Trypanosoma evansi in Camels (Camelus dromedaries) in South Darfur State (Journal of Veterinary Medicine and Animal Production, 2021)
Trypanosoma evansi infection is considered as most important disease of camel in the Sudan. The aim of this study was to investigate the T. evansi infection of dromedary camel, using the parasitological, serological and molecular tools. A two-year three seasons study of the prevalence of trypanosomosis in camels (Camelus dromedarus) was conducted in Nyala area (South Darfur State). Jugular vein blood samples were randomly collected from 350 camels and examined parasitologically by Giemsa stained blood smears (GSBS) for the presence of the trypanosomes, serologically for detection of anti-trypanosomal antibodies by card agglutination test (CATT) and molecularly for detection of the T. evansi amino- acid sequence through PCR using T. brucei spp specific primers. Out of the 350 samples 37(10.6%) were positive by smears, and 126 (36%) were positive by CATT through anti-trypanosomal antibodies, while 140 (40%) were positive by PCR. The obtained results showed that PCR have higher sensitivity and specificity (90%), while CATT and smears gave less sensitivity 69% and 31% respectively. The prevalence was significantly greater in the rainy season than the dry season.